Sustaining seas : oceanic space and the politics of care / edited by Elspeth Probyn, Kate Johnston, and Nancy Lee. - Probyn, Elspeth, 1958-; Johnston, Kate, 1979-; Lee, Nancy, 1986- (Rowman & Littlefield International, 2020)
This edited book emerges from conversations across several disciplines, and including practitioners of different specialities (artists, writers, planners, policy makers) about how to sustain the seas, as they sustain us. 'Sustaining Seas' aims to build a better understanding of what it means to care for aquatic places and their biocultural communities. The book is truly interdisciplinary and brings together a wide range of authors including, academics from diverse fields (architecture, science, cultural studies, law), artists, fisheries managers, and indigenous traditional owners.